(untitled) (African Disability Rights Yearbook, 2025)
This paper investigates the often-neglected topic of disability-inclusive climate action, focusing on the recommendations from the Committee on the Rights of Persons with Disabilities for African countries. The author’s analysis reveals a consistent emphasis by the Committee on climate change in its Concluding Observations, particularly in relation to adaptive capacity for climate-related disasters. Key recommendations typically encompass emergency and disaster risk reduction strategies, the provision of information in accessible formats, and the establishment of engagement channels with disability representative organisations. However, the Committee’s climate change discussions fail to adequately address the unique attributes of the African region and its individual countries, leaving several crucial issues unresolved. These issues encompass the need for improved international cooperation and a focus on disability sub-groups with climate-related concerns. The paper advocates for the Committee to intensify its efforts to address disability-inclusive responses to climate change, including general recommendations for the inclusion and recognition of the diversity of persons with disabilities and astrategy for international collaboration on climate change.